Role of KSP Inhibitors as Anti-Cancer Therapeutics: An Update - Chamariya, Rinkal; Suvarna, Vasanti (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Regardless of the growing discovery of anticancer treatments targeting cancer-specific pathways, cytotoxic therapy still maintained its abundant clinical significance because tumours harbor a greater population of actively dividing cells than normal tissues. Conventional anti-mitotic agents or microtubule poisons acting on the major mitotic spindle protein tubulin have been effectively used in clinical settings for cancer chemotherapy over the last three decades. However, the use of these drugs is associated with limited clinical utility due to serious side effects such as debilitating and dose-limiting peripheral neuropathy, myelosuppression, drug resistance, and allergic reactions. Therefore, research initiatives have been undertaken to develop novel microtubule motor proteins inhibitors that can potentially circumvent the limitations associated with conventional microtubule poisons. Kinesin spindle proteins (KSP) belonging to the kinesin-5 family play a crucial role during mitosis and unregulated cell proliferation. Evidence from preclinical studies and different phases of clinical trials have presented kinesin spindle protein as a promising target for cancer therapeutics. Kinesin spindle protein inhibitors causing mitosis disruption without interfering with microtubule dynamics in non-dividing cells offer a potential therapeutic alternative for the management of several major cancer types and are devoid of side effects associated with classical anti-mitotic drugs. This review summarizes recent data highlighting progress in the discovery of targeted KSP inhibitors and presents the development of scaffolds, structure-activity relationships, and outcomes of biological and enzyme inhibition studies. We reviewed the recent literature reports published over the last decade, using various electronic database searches such as PubMed, Embase, Medline, Web of Science, and Google Scholar. Clinical trial data till 2021 was retrieved from ClinicalTrial.gov. Major chemical classes developed as selective KSP inhibitors include dihydropyrimidines, β-carbolines, carbazoles, benzimidazoles, fused aryl derivatives, pyrimidines, fused pyrimidines, quinazolines, quinolones, thiadiazolines, spiropyran, and azobenzenes. Drugs such as filanesib, litronesib, ispinesib have entered clinical trials; the most advanced phase explored is Phase II. KSP inhibitors have exhibited promising results; however, continued exploration is greatly required to establish the clinical potential of KSP inhibitors.
Keywords: filanesib